2013
DOI: 10.1002/rcm.6665
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope analysis of dissolved inorganic carbon (DIC) and dissolved organic carbon (DOC) in natural waters – Results from a worldwide proficiency test

Abstract: This study indicates that scatter in δ(13)CDIC isotope data can be in the range of several per mil for samples from extreme environments (geothermal waters) and may not yield reliable information with respect to dissolved carbon (petroleum wells). The analyses of lake water and seawater also revealed a larger than expected difference and researchers from various disciplines should be aware of this. Evaluation of analytical procedures of the participating laboratories indicated that the differences cannot be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Our δ 13 C‐DIC intercomparison study involving 16 groups worldwide showed between‐lab reproducibility of uncorrected raw values (±0.11‰) comparable to that reported from the only previous published interlaboratory comparison of seawater analyses (van Geldern et al ), which was limited to only five groups. The level of between‐lab reproducibility was also not statistically different from the magnitude and variability of offsets between historical cruise data sets detected by crossover analysis.…”
Section: Conclusion and Recommendationssupporting
confidence: 87%
See 2 more Smart Citations
“…Our δ 13 C‐DIC intercomparison study involving 16 groups worldwide showed between‐lab reproducibility of uncorrected raw values (±0.11‰) comparable to that reported from the only previous published interlaboratory comparison of seawater analyses (van Geldern et al ), which was limited to only five groups. The level of between‐lab reproducibility was also not statistically different from the magnitude and variability of offsets between historical cruise data sets detected by crossover analysis.…”
Section: Conclusion and Recommendationssupporting
confidence: 87%
“…In this study, the between‐lab reproducibility ( δ 13 C stdev ) for both RM and DSW, before correction based on RMs but after outlier removal, was 0.11‰. The only previously published assessment by van Geldern et al () involved only five groups and reported between‐lab reproducibility ( δ 13 C stdev ) as low as 0.07‰ for results from four laboratories but reaching 0.47‰ when results from all five laboratories were included.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Over the last decade, WCO analysis has become a routine analytical technique . However, a unified world‐wide laboratory protocol for selecting soluble international isotope reference materials has not yet been established, creating the potential for inconsistency in results obtained by different laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the large quantities of chlorine gas produced as a byproduct of WO in seawater, causes the rapid corrosion of some parts of the reaction vessel, the fouling of the halide/sulfide traps, and the rapid exhaustion of reducing agents. As part of a recent intercomparison study, two different labs using wet chemical oxidation measured the δ 13 C-DOC of a single seawater sample to be -9.3 and -11.0‰ (Van Geldern et al 2013), an 8 to 10‰ δ 13 C enrichment over values generally reported for seawater DOC (-20.1 to -22.9‰;Bauer 2002 and references therein), probably caused by a WO method artifact.…”
mentioning
confidence: 99%